Upaya Meningkatan Kreativitas Melalui Kegiatan Bermain Origami Pada Anak Kelompok B di TK Pertiwi II Purwosuman Sidoharjo Sragen Tahun Pelajaran 2016/2017 - Hartanto, Rika Dwi; , Drs.Surtikanti, M.Pd (2017)
Origami is a handicraft using paper as raw material to make various shapes such as animals, decorations, functional tools, visual aids and other creations. For kindergarten children, paper folding activity is one of interesting and fun creative play activities. The activity can develop competences of thought, imagination, art sense and skill of children. Purpose of the research is to improve children creativity by using origami in Group B students of Pertiwi II Kindergarten of 2016 located in Purwosuman, Sidoharjo, Sragen. The research is a classroom action research. Data was collected by using observation, interview, documentation and field records. Design of the classroom action research consisted of four stages, namely (1) planning, (2) implementation, (3) observation, (4) reflection. Results of calculation for each cycle of rough motor development of children obtained 42.6% at precycle, and after implementation of action at cycle I, the value was 60.32%, and 82.18% at cycle II. Therefore, efforts of creativity improvement by using origami playing for Group B students of Pertiwi II Kindergarten of 2016 can be said as successful because it had met the determined maximum percentage, namely 80%.